2018
DOI: 10.15446/dyna.v85n207.72347
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of lead using atomic absorption spectrometry in thermoformed and biodegradable flexible films made from cassava (Manihot esculenta crantz)

Abstract: Recently developed biopolymers can contain lead due to contamination from the origin of the material used to make them. A method for determining the presence of lead is proposed, using GF-AAS in thermoformed and biodegradable flexible films and flour and starch samples from Cassava. Acid digestion with reflux was optimized and the statistical quality parameters were standardized. The graphite furnace heating program was adjusted through pyrolysis and atomization curves. The working range was from 2.0 to 7.0 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Quantities of Zn ranged from 1.13 to 2.14 mg/L. Literature reports for these same samples the detection of mercury 6.4 mg/L, 24 selenium 5.4 mg/L, 33 while arsenic, 32 Lead 34 and Cadmium 10 were not detected. These findings may be associated to the cultivation areas which are naturally rich in these toxic metals.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Quantities of Zn ranged from 1.13 to 2.14 mg/L. Literature reports for these same samples the detection of mercury 6.4 mg/L, 24 selenium 5.4 mg/L, 33 while arsenic, 32 Lead 34 and Cadmium 10 were not detected. These findings may be associated to the cultivation areas which are naturally rich in these toxic metals.…”
Section: Resultsmentioning
confidence: 76%
“…In previous studies, the presence of others metals such as mercury, arsenic, selenium, lead and cadmium in these samples was detected. 10,24,[32][33][34] Levels of mercury up to 67.2 mg/L, arsenic below 1.9 mg/L, selenium up to 62.0 mg/L, lead up to 3.2 mg/L and cadmium ranging from 21 mg/L to 89 mg/L were found.…”
Section: Resultsmentioning
confidence: 99%
“…In these flexible films, mercury was reported to be undetectable to 127.3 mg/kg, 56 arsenic was undetected, 57 and selenium was reported to be undetectable to 122 mg/kg. 58 Other authors reported that selenium can decrease the Cd concentrations and increase the growth in vegetables. 59 In thermoformed and biodegradable flexible films, the values of heavy metals accumulated were higher for mercury than for selenium, Cd, and arsenic, suggesting that absorption and bioaccumulation depend upon the availability of metals.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors found mercury, arsenic, and selenium present in these thermoformed samples. Del Castillo et al 56 determined mercury ranging from undetectable to 1343.4 mg/ kg, Alvira et al 57 determined arsenic with concentrations of less than the LOQ (39.2 mg/kg), and Rada-Mendoza et al 58 found selenium ranging from undetectable to 1240.0 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…All samples were measured in triplicate, and the mean values were expressed as µgPb/Kg. (Rada-Mendoza et al, 2018) The wavelength used in the analysis was 283.3 nm. Lead has the energy of 7.0134.10-8 Joule.…”
Section: Methodsmentioning
confidence: 99%